Sarcoid Associated with Infection by Habronema spp. in Equines in Brazil - Firmino, Millena de Oliveira; Alves, Rodrigo Cruz; Olinda, Roberio Gomes; Carneiro Júnior, Manoel Simões; Neto, Eldinê Gomes de Miranda; Riet-Correa, Franklin; Dantas, Antônio Flávio Medeiros (Acta Scientiae Veterinariae, 2016)
Background: Equine sarcoid, supposed to be caused by infection with bovine papillomavirus type 1 or 2, is usually observed in previously traumatized skin areas, including lesions of habronemosis due to inoculation of third stage larvae in ulcerated wounds by Musca domestica or Stomoxys calcitrans. Little is known about the occurrence of diseases associated with equine sarcoid, mainly because limitations on clinical diagnosis, due to the different skin diseases that have to be considered as differential diagnoses. This report aimed to describe three cases of equine sarcoid associated with habronemosis in horses in the semiarid region of Northeastern Brazil. Cases: Three cases of sarcoid associated with habronemosis in equines were diagnosed at the Animal Pathology Laboratory of the Veterinary Hospital of the Federal University of Campina Grande, Patos, Paraíba. Case 1. A 5-year-old female showed in the ventral branch of the mandible a nodule of 3 cm in diameter, partially covered with skin and hair intercepted by areas of irregular surface with yellow-red ulcerations. The cut surface was formed by whitish and firm tissue. Case 2. It was a biopsy from a 4-year-old mare, who was not informed of the macroscopic characteristics of the lesion. Case 3. A 5-year-old horse presenting a nodular mass in the region of the tarsal-metatarsal joint, measuring 8.0x5.0x3.0 cm with an irregular, ulcerated, red-blackish surface. The cut surface was firm and whitish with brownish punctate areas. Microscopically all the lesions were classified as equine sarcoid of mixed type with abundant collagen fibers and randomly extensive proliferation of fibroblasts in the dermis. These fibroblasts had an elongated and weakly eosinophilic cytoplasm, rounded nucleus and prominent nucleoli. There were low mitotic activity. Hyperplasia, hyperkeratosis and sometimes ulcerated areas covered by serous cellular scabs were observed in the skin. Multifocal coalescing, granulomatous and eosinophilic lesions were observed within the neoplastic tissue. Cylindrical structures with an elongated thick eosinophilic outer cuticle and obvious side spicules, morphologically compatible with larvae Habronema spp, surrounded by inflammatory cells and cellular debris were observed in Cases 1 and 2. In case 3, intralesional larvae were not observed, but histologic lesions had a similar pattern than cases 1 and 2. Discussion: In these cases the affected animals presented simultaneously a mixed lesion of sarcoid and habronemosis, which leads to complications in clinical diagnosis and difficulties to institute appropriate therapy. Histopathological examination of such lesions is necessary because should characterize their morphology and the causative agent, discarding the other differential diagnoses. The combination of these two conditions can probably be related to the fact that sarcoid may develop up in places previously traumatized, such us lesions of habronemosis. It is important to differentiate these lesions from other skin diseases such as granulation tissue, pythiosis, squamous cell carcinoma and fibroid. Though the occurrence of sarcoid and simultaneous habronemosis in horses is rare in equine medicine, clinicians and pathologists who work with diagnosis may sporadically encounter similar cases, hence the importance of histopathologic analysis of skin samples, as this may help definition of the a etiology and also the institution of therapeutic measures and prognosis of affected animals. Keywords: equine skin disease, skin neoplasms, parasitic infection.